Crosstalk between ferroptosis and innate immune in diabetic kidney disease: mechanisms and therapeutic implications - Wang, Jinyang; Shi, Haonan; Yang, Ye; Gong, Xueli (Frontiers in Immunology, 2025)
Diabetic kidney disease (DKD) is a prevalent complication of diabetes mellitus (DM), and its incidence is increasing alongside the number of diabetes cases. Effective treatment and long-term management of DKD present significant challenges; thus, a deeper understanding of its pathogenesis is essential to address this issue. Chronic inflammation and abnormal cell death in the kidney closely associate with DKD development. Recently, there has been considerable attention focused on immune cell infiltration into renal tissues and its inflammatory response’s role in disease progression. Concurrently, ferroptosis—a novel form of cell death—has emerged as a critical factor in DKD pathogenesis, leading to increased glomerular filtration permeability, proteinuria, tubular injury, interstitial fibrosis, and other pathological processes. The cardiorenal benefits of SGLT2 inhibitors (SGLT2-i) in DKD patients have been demonstrated through numerous large clinical trials. Moreover, further exploratory experiments indicate these drugs may ameliorate serum and urinary markers of inflammation, such as TNF-α, and inhibit ferroptosis in DKD models. Consequently, investigating the interplay between ferroptosis and innate immune and inflammatory responses in DKD is essential for guiding future drug development. This review presents an overview of ferroptosis within the context of DKD, beginning with its core mechanisms and delving into its potential roles in DKD progression. We will also analyze how aberrant innate immune cells, molecules, and signaling pathways contribute to disease progression. Finally, we discuss the interactions between ferroptosis and immune responses, as well as targeted therapeutic agents, based on current evidence. By analyzing the interplay between ferroptosis and innate immunity alongside its inflammatory responses in DKD, we aim to provide insights for clinical management and drug development in this area.